Pelatihan Kewirausahaan Islami dan Pembuatan Es Krim bagi Siswa SMP Menghafal Qur’an Khairu Ummah Makassar - Imaduddin Murdifin (Pangulu Abdi: Jurnal Pengabdian Kepada Masyarakat, 2023)
Abstract. Islamic Entrepreneurship Training at SMPMQ Khairu Ummah School is carried out to motivate students to become entrepreneurs from an early age. An illustration of a business that has the potential to be developed is also exemplified, namely the ice cream culinary business. Ice cream is a dairy product that is widely consumed and is a source of fat, protein, carbohydrates and calcium, especially for children; but has a critical point in terms of the halalness of its additional ingredients, such as milk protein, stabilizer, emulsifier, and flavoring. The method used is counseling in the form of lectures accompanied by interactive discussions and guided practice in making ice cream. The results of the evaluation showed that there was an increase in the knowledge and skills of about 80% of the participants regarding the need for entrepreneurship and the Islamic way of entrepreneurship; and how to make halal and thayyib ice cream. Keywords: Islamic Entrepreneurship, SMPMQ Khairu Ummah, Ice Cream, Halal and Thayyib